IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SDN 1 MRANTI KEC. PURWOREJO KAB. PURWOREJO - Musolin, Muhlil (Universitas Nurul Jadid, 2019)
School Based Management (SBM) can be interpreted as the use of school-based resources in the teaching or learning process. The research objective is to find out: Implementation of School Based Management in SDN 1 Mranti Kec. Purworejo Kab. Purworejo in the 2018/2019 school year. This research is a qualitative descriptive study. Informants or informants in this study are the principal, teachers, employees. Data collection techniques in this study were observation, interviews, documentation, data analysis in this study, namely: data reduction, data presentation, and drawing conclusions. The results showed SDN 1 Mranti,. Purworejo, Purworejo has implemented School Management Components namely curriculum management and teaching programs, management of teaching staff, student management, financial management and financing, management of educational facilities and infrastructure, management of school relations with the community, and management of special services (library management, health management (UKS) , and school security management).